2012
DOI: 10.1590/s0004-282x2012000900010
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications following bariatric surgery

Abstract: Objective: It was to report on Brazilian cases of neurological complications from bariatric surgery. The literature on the subject is scarce. Method: Cases attended by neurologists in eight different Brazilian cities were collected and described in the present study. Results: Twenty-six cases were collected in this study. Axonal polyneuropathy was the most frequent neurological complication, but cases of central demyelination, Wernicke syndrome, optical neuritis, radiculits, meralgia paresthetica and compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In another study, the peroneal nerve was most susceptible for neuropathy [20]. One case of acute brachial neuropathy and acute brachial radiculitis, also known as Parsonage–Turner syndrome, has been reported [21]. Rapid weight loss postsurgery is the most commonly observed risk factor in these conditions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, the peroneal nerve was most susceptible for neuropathy [20]. One case of acute brachial neuropathy and acute brachial radiculitis, also known as Parsonage–Turner syndrome, has been reported [21]. Rapid weight loss postsurgery is the most commonly observed risk factor in these conditions.…”
Section: Resultsmentioning
confidence: 98%
“…We identified two high‐quality retrospective controlled cohort studies [15,16], one prospective case series [17], four retrospective case series [18–21], five high‐quality review articles [22–26], and four studies that analyzed the pharmacokinetics of neuropathic analgesics in the PBS scenario [27–30]. No randomized controlled trials, controlled trials on identification of incidence, precise pathology, and management of pain or evidence‐based protocols for therapeutic management were identified.…”
Section: Resultsmentioning
confidence: 99%
“…It is a potential cause for malabsorption or limited absorption surface resulting in nutritional deficiency-related neuropathies and myelopathy. Nutritional complications following BS may occur for a variety of reasons including reduced dietary intake, reduced gastric acid, inadequate intrinsic factor secretion, or lack of nutrient exposure to the duodenum [4]. Neurological complications following BS in two prior large studies are reported to occur in 5% -16% of patients according to a review of 18 surgical series reported between 1976 -2004 [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews and studies on “bariatric beriberi” and neurologic complications following bariatric surgery have been published 54 , 86 . ‐ 94 In a nonrandomized controlled study, Thaisetthawatkul et al 89 evaluated the frequency of peripheral neuropathy in post–bariatric surgery patients compared with age‐ and gender‐matched controls of obese patients undergoing cholecystectomy.…”
Section: Post–bariatric Surgery Patientsmentioning
confidence: 99%